Do Partial Acquisition Announcements Affect the Stock Market? Evidence from Indian Chemical and Pharmaceutical Industry - R. Kalia; S. Srivastav; R. Mittal; I. Gupta (Финансы: теория и практика, 2024)
The purpose of the study is to find out whether partial acquisitions enhance the shareholders’ wealth of the acquiring firms in the Indian chemical and pharmaceutical industry. Partial acquisitions are the unique form of corporate restructuring and have become the choice of most companies, which makes this study relevant to explore in the current context. The objective of the study is to evaluate the impact of partial acquisition announcements on the stock price return of the acquiring companies listed on the Indian Stock Exchange and test the statistical significance of the returns for different event windows. The novelty of the study is that it examines the announcement effects of partial acquisitions on the shareholders’ wealth of acquiring firms in the Indian chemical and pharmaceutical industry. Event Study Methodology is used with different event windows along with parametric and non-parametric tests to verify the statistical significance of returns. The research results shows that the announcements of partial acquisitions generate positive reaction in the shorter event windows of (–1, 0), (0, +1) and (–1, +1) but this reaction is only temporary and quickly diluted over the longer event window of (–10, +10). Hence, the study concluded that the shareholders can have a significant return in a shorter event window around the announcements of partial acquisitions. The results of the study are useful for various stakeholders including shareholders, investors, and managers of the companies of the selected industries in their decision-making during partial acquisitions.